Clinical characteristics and outcome predictors of a Chinese childhood-onset myasthenia gravis cohort - Yang, Lifen; Tang, Yulin; He, Fang; Zhang, Ciliu; Kessi, Miriam; Peng, Jing; Yin, Fei (Frontiers in Pediatrics, 2022)
Myasthenia gravis is an organ-specific autoimmune disease. Currently there is no universal guidelines for childhood-onset myasthenia gravis, therefore, treatment strategies are usually based on the guidelines from adult myasthenia gravis patients. In order to contribute in the process of the development of the universal childhood-onset myasthenia gravis guideline, we have summarized the clinical characteristics, treatment strategies, outcome and the related predictors of childhood-onset myasthenia gravis. We recruited 343 childhood-onset myasthenia gravis cases who were followed up at the Department of Pediatrics, Xiangya Hospital from June, 2010 to December, 2019. The data about clinical characteristics, treatments and outcome were collected and analyzed. Among of the 343 cases, 164 cases were followed up for longer than 2 years, of whom 142 still remained with ocular myasthenia gravis at the endpoint. About the treatments, 27 cases (27/164) accepted pyridostigmine only while the rest accepted glucocorticoid and/or other immunosuppressants. At the endpoint, the proportion of optimal outcome was 66.2% in the group remaining with ocular myasthenia gravis and 31.8% in the generalized myasthenia gravis group. Multivariate logistic regression analysis revealed that generalized myasthenia gravis type and positive status of antibodies against acetylcholine receptors were the independent risk factors for poor outcome. In conclusion, our childhood-onset myasthenia gravis patients present mainly as ocular myasthenia gravis, adequate immunotherapy improve the long-term outcome, and generalized myasthenia gravis phenotype as well as positive status of antibodies against acetylcholine receptors relate to poor outcome.